Editorial Note Vol.15 - Shakya, Shanta Man (Nepalese Horticulture, 2021)
The Editorial Committee takes pleasure to present before you the 15th volume of the journal “Nepalese Horticulture”, an official publication of Nepal Horticulture Society (NHS) established in 1990, amid Covid pandemic crisis. NHS has been regularly publishing the workshop proceedings of the NH Seminars, books, manuals, reviews and other horticulture related publications as per the country’s current situation and public demand. It holds together almost all the horticulturists in Nepal as well as those who are abroad, working in diverse fields related to horticulture including private sector. Nepalese Horticulture is the outcome of scientific research studies, investigations and critical reviews of the articles which are peer reviewed, with an objective of achieving rational livelihood, food security, poverty alleviation, qualitative public health and pollution free environment in the country as foreseen by the state policies and plans as well as millennium goals. The Committee acknowledges the valuable contributions of the authors whose articles have been published in this issue as well as those authors whose articles could not be accommodated in this issue because of some technical reasons. Similarly, it also acknowledges the valuable supports of the peer reviewers for their painstaking work of reviewing the articles. It further encourages researchers, development workers and private entrepreneurs for their continued support with their authorship enabling us to bring out the present issue. On top of its regular publication in printed form it has also been digitalized and uploaded for the readers. The Committee gratefully acknowledges the cooperation and supports extended by various institutions and individuals who have made the publication of this issue possible. It also extends thanks to all the subscribers, readers and well-wishers of the journal and looks forward to their continued supports in the future, too. Thanks and be safe!